Rancang Bangun Website Promosi Pada Sapo Rumbia Villa and Cottage - Sinaga, Mikha; Sembiring, Nita; Sianturi, Charles; Ginting, Erwin; Elisabeth, Noprita; Ramadhani, Ivo (Publikasi Pengabdian Masyarakat, 2022)
Promotion is an important part of marketing goods and services. Promotions can contain information that can attract consumers' interest in the goods and services we offer. With the promotion, it is hoped that there will be an increase in sales figures for the product or service being promoted. Sapo Rumbia Villa and Cottage markets its villas and lodging rooms through social media such as Facebook and Instagram as well as online booking applications such as Oyo. Sapo Rumbia Villa and Cottage only contains information related to villas and lodging in the form of Facebook and Instagram page statuses, not through advertisements on the social media. The Oyo application only contains information related to lodging rooms and villas. The information provided is also very limited, only regarding the price and facilities in the room or villa. In fact, the natural scenery around Sapo Rumbia Villa and Cottage is very beautiful to look at. Sapo Rumbia Villa and Cottage is surrounded by Gundaling Hill, local people's plantations, and beautiful views of Mount Sibayak. The community service activities carried out have the aim of promoting Sapo Rumbia Villa and Cottage and providing information related to Sapo Rumbia Villa and Cottage to the wider community. This activity also has several benefits, namely helping the management in promoting their villas and inns, making it easier for the public to obtain information related to Sapo Rumbia Villas and Cottages, and increasing Sapo Rumbia's income from the promotions that have been made. The result of this activity is to add promotional media for Sapo Rumbia Villa and Cottage, so that it can increase public knowledge of the natural beauty around Sapo Rumbia Villa and Cottage which can add positive value to Sapo Rumbia Villa and Cottage.